A novel semi-theoretical model for hydraulic conductivity prediction considering temperature effect - Jiahua Li; Shiwan Chen; Ruyun Wu; Yuhang Zhu; Senyou An (Case Studies in Thermal Engineering)
It is of great significance to accurately characterize fluid migration within fractures under thermal-mechanical coupling condition for deep ground engineering, especially for the nuclear waste disposal engineering. Previous efforts characterizing hydraulic properties of fractures have focused on room temperature, and it is difficult to deep understand the deformation-seepage coupling process of rock fractures under temperature. Thus, models derived from in this condition have been limited in their predictive ability for fracture seepage. This paper addresses the key challenge through well-designed experiments, combined with the improved BB model and the cubic law. The fracture deformation was separated from single-fractured granite during normal cyclic loading. The deformation and hydraulic properties of granite fractures under thermal-mechanical coupling were analyzed in detail. A linear relationship between hydraulic aperture and mechanical aperture considering temperature effect is established. A stress-deformation-seepage model considering temperature and cyclic loading history effect is proposed, and the accuracy of the model is verified. This study can provide reference for nuclear waste geological disposal project.